Iridium carbonyl complexes as model homogeneous catalysts - Engelbrecht, Ilana (University of the Free State, 2010)
The aim of this study was to investigate model iridium carbonyl complexes as homogeneous catalyst precursors for processes such as olefin hydroformylation. The hydroformylation of alkenes is one of the most important applications of transition metal based homogeneous catalysis. The coordination chemistry of rhodium and iridium phosphine complexes plays a major role in the understanding of basic organometallic reactions and homogenous catalytic processes.1 The diversity of tertiary phosphines in terms of their Lewis basicity and bulkiness render them excellent candidates to tune the reactivity of square-planar complexes towards a variety of chemical processes, such as oxidative addition and substitution reactions.2 Iridium(I) complexes of the type trans-[Ir(acac)(CO)(PR3)2] (acac = acetylacetonate, PR3 = PPh3, PPh2Cy, PPhCy2, PCy3) were synthesized and characterized by infrared (IR) and nuclear magnetic resonance spectroscopy (NMR). The X-ray crystallographic determinations of trans-[Ir(acac-κO)(CO)(PPhCy2)2] and trans-[Ir(acac-κ2O,O)(CO)(PCy3)2] were successfully completed and are compared with literature. Both complexes crystallize in monoclinic crystal systems, C2/c. Only trans-[Ir(acac-κO)(CO)(PPhCy2)2] co-crystallized with solvent molecules as part of the basic molecular unit cell, though these solvent molecules show no apparent impact on the steric packing of the basic organometallic group. This delivered information as to the identification of products formed during the kinetic studies and increased the available information of these rare compounds in literature.3 Two reactions were observed when rapid substitution of CO for PPh3 in [Ir(acac)(CO)2] was investigated in methanol as solvent by use of cryo temperature photo-multiplier Stopped-flow spectrophotometry. The first reaction followed the general rate law for square planar substitution reactions where rate = (ks + k1[L])([substrate]) with pseudo first-order rate constant kobs1 = ks + k1[L] and k1 the second-order rate constant for the substitution reaction. This indicated that the first step involves the substitution of one carbonyl group forming [Ir(acac)(CO)(PPh3)]. Linear plots of kobs against concentration of the incoming PPh3 ligand passed through the origin implying that ks ≈ 0, signifying that the solvent does not significantly contribute to the reaction rate and the rate law simplifies to kobs1 = k1[L], with k1 = 92.5(3) x 103, 77(3) x 103, 66(1) x 103 and 58(2) x 103 M-1 s-1 at -10, -20, -30 and -40 °C, respectively. The temperature dependence was determined with ΔHk1 = 5.8(6) kJ mol-1 and the large negative values obtained for standard entropy change of activation, ΔSk1 = -127(2) J K-1 mol-1, suggests an associative substitution mechanism. The second reaction is defined by limiting kinetic behaviour and is indicative of a two-step process involving the stepwise rapid formation of trans-[Ir(acac)(CO)(PPh3)2] with preequilibrium K2 = 1(3) x 102, 4(1) x 102, 7(2) x 102 M-1 at -20, -30 and -40 °C, respectively and rate-determining second step being the ring opening of the acac- ligand to yield trans-[Ir(acac-κO)(CO)(PPh3)2] with k3 = 18(5) x 101, 10(1) x 101, 4.7(4) x 101 M-1 s-1 at -20, -30 and -40 °C, respectively. The temperature dependence for the second reaction was determined with ΔHk3 = 30.8(3) kJ mol-1 and ΔSk3 = -79(1) J K-1 mol-1.

Die doel van hierdie studie was om model iridium-karboniel komplekse as homogene katalisvoorlopers in prosesse soos olefien hidroformilering te ondersoek. Die hidroformilering van alkene is een van die belangrikste toepassings van oorgangsmetaalgebaseerde homogene katalise. Die koördinasiechemie van rodium- en iridium-fosfien komplekse speel `n belangrike rol in die verstaan van basiese organometaliese reaksies vir homogene katalitiese prosesse. Die verskeidenheid van tersiêre fosfiene in terme van hulle Lewis basisiteit en bonkigheid maak hulle uitstekende kandidate om die reaktiwiteit van vierkantig-planêre komplekse te verstel ten opsigte van `n verskeidenheid chemiese prosesse soos oksidatiewe addisie en substitusie reaksies. Iridium(I) komplekse van die tipe trans-[Ir(acac)(CO)(PR3)2] (acac = asetielasetonaat, PR3 = PPh3, PPh2Cy, PPhCy2, PCy3) is gesintetiseer en gekarakteriseer deur infrarooi (IR) en kern magnetiese resonans spektroskopie (KMR). Die X-straal kristallografiese bepaling van trans-[Ir(acac-κO)(CO)(PPhCy2)2] en trans-[Ir(acac-κ2O,O)(CO)(PCy3)2] is suksesvol voltooi en vergelyk met literatuur. Beide komplekse kristalliseer in monokliniese kristalstelsels, C2/c. Slegs trans-[Ir(acac-κO)(CO)(PPhCy2)2] ko-kristalliseer met oplosmiddel molekule as deel van die basiese molekulêre eenheidsel; hierdie oplosmiddel molekule het egter geen ooglopende impak op die steriese pakking van die basiese organometalliese groep nie. Dit lewer inligting ten opsigte van die identifisering van produkte wat gedurende die kinetiese studies gevorm is en verhoog die beskikbare inligting van hierdie skaars verbindings in die literatuur. Twee reaksies is waargeneem tydens die ondersoeke van vinnige substitusie van CO met PPh3 in [Ir(acac)(CO)2] in metanol as oplosmiddel deur middel van lae temperatuur foto-vermenigvuldiger gestopde-vloei spektrofotometrie. Die eerste reaksie volg die algemene tempowet vir vierkantig-planêre substitusiereaksies waar Tempo = (ks + k1[L])([substraat]) met pseudo eerste-orde tempokonstante kobs1 = ks + k1[L] en k1 die tweedeorde tempokonstante vir die substitusiereaksie. Dit dui aan dat die eerste stap die substitusie van een karbonielgroep om [Ir(acac)(CO)(PPh3)] te vorm behels. Liniêre grafieke van kobs teenoor konsentrasie van die inkomende PPh3 ligand gaan deur die oorsprong, wat impliseer dat ks ≈ 0 en aandui dat die oplosmiddel nie beduidend bydra tot die reaksietempo nie en dat die tempowet vereenvoudig na kobs1 = k1[L], met k1 = 92.5(3) x 103, 77(3) x 103, 66(1) x 103 en 58(2) x 103 M-1 s-1 by -10, -20, -30 en -40 °C, onderskeidelik. Die temperatuurafhanklikheid is bepaal met ΔHk1 = 5.8(6) kJ mol-1 en die groot negatiewe waardes verkry vir standaard verandering van aktiveringsentropie, ΔSk1 = -127(2) J K-1 mol-1, stel `n assosiatiewe substitusie meganisme voor. Die tweede reaksie word gedefinieer deur beperkende kinetiese gedrag en is aanduidend van `n twee-stap proses wat betrokke is by die stapsgewyse vinnige vorming van trans-[Ir(acac)(CO)(PPh3)2] met pre-ekwilibrium K2 = 1(3) x 102, 4(1) x 102, 7(2) x 102 M-1 teen onderskeidelik -20, -30 en -40 °C en `n tempobepalende tweede stap wat die ring-opening van die acac- ligand behels om te lei tot trans-[Ir(acac-κO)(CO)(PPh3)2] met k3 = 18(5) x 101, 10(1) x 101, 4.7(4) x 101 M-1 s-1 teen onderskeidelik -20, -30 en -40 °C. Die temperatuurafhanklikheid vir die tweede reaksie is bepaal met ΔHk3 = 30.8(3) kJ mol-1 en ΔSk3 = -79(1) J K-1 mol-1.
Dissertation (M.Sc. (Chemistry))--University of the Free State, 2010
Keywords: Iridium; Acetylacetonate; Phosphine; Substitution; Kinetics; Iridium catalysts; Substitution reactions; Chemical kinetics; Ligands